Front Cover, Volume 40, Issue 9. Issue 9 (13th September 2019) - Padilla, Natàlia; Moles‐Fernández, Alejandro; Riera, Casandra; Montalban, Gemma; Özkan, Selen; Ootes, Lars; Bonache, Sandra; Díez, Orland; Gutiérrez‐Enríquez, Sara; de la Cruz, Xavier
Abstract : Outside Front Cover : The cover image is based on the Special Article BRCA1‐ and BRCA2‐specific in silico tools for variant interpretation in the CAGI 5 ENIGMA challenge by Natàlia Padilla et al., https://doi.org/10.1002/humu.23802 . Cover design: Selen Özkan and Xavier de la Cruz.